The Efficiency of Higher Education and Training Economics in the Arab Gulf Countries in the Light of the Global Competitiveness Index (GCI) Standards (2010- 2018) - Comparative analytical study - Al- Badrani, Badr Salem (Journal of Educational and Psychological Sciences, 2020)
The study aimed to discuss Arab Gulf states in the global competitiveness index issued annually by the World Economic Forum during the period (2010- 2018) in terms of the economic efficiency index, and the efficiency factor of higher education and training economics. That is for the hypothesis claimed that there is an effect of the efficiency of higher education and training economics in Arab Gulf states on the economic efficiency considering global competitiveness index standards. The study analyzed the situation of each of Arab Gulf states (Saudi Arabia- Kuwait- United Arab Emirates- Oman- Bahrain- Qatar) in terms of the overall rate and ranking, and used first- degree mathematical equations with one, two and three variable to reach the result of the situation of Arab Gulf states regards the top-ranking countries and the backward ranking countries, whether in the economic efficiency or in the efficiency factor of higher education and training economics. The study used a mathematical equation to analyze the effect of the efficiency factor of higher education and training economics in Arab Gulf states on the economic efficiency, and came out with several results based on mathematical equations and economic aspects with regard to the efficiency factor of higher education and training economics in Arab Gulf states. The study found that the degree of impact of the efficiency factor of higher education and training economics on the economic efficiency in Arab Gulf states in light of global competitiveness index standards are considered medium to tend to rise, reaching (11.20%) out of (17%).